Patients with terminal chronic disease in the adult emergency Service of a tertiary hospital: Pacientes con enfermedad crónica terminal en el servicio de emergencia de adultos de un hospital terciario - Amado-Tineo, José (2019)
Introduction: Patients with chronic terminal disease frequently come to emergency department of reference hospitals. Objectives: To determine frequency of chronic terminal disease in patients admitted to emergency department, identify invasive procedures and compare oncological with non-oncological patients. Methods: Cross-sectional study in patients older than 18 years old, admitted to emergency department of a tertiary hospital, November 2017. Criteria for terminal disease: Clinical stage IV cancer, severe cognitive deterioration or total functional dependence plus diagnosis of dementia, neurological sequelae, dependence of oxygen, glomerular filtration rate <30 ml / min, Child C cirrhosis, or left ventricular ejection fraction <20%. Statistical analysis with Mann-Whitney U and Chi square tests. Results:10.7% (172 of 1604 admissions) of admitted patients presented criteria of chronic terminal disease, with oncological cause 21.5% (37/172) and non-oncological 78.5% (135/172). In oncological patients, the median age was 70 years and was female 59.5%, while in non-oncological 84 years and 57% of women (p <0.01 and 0.79, respectively). 41% (71/172) were admitted by shock-trauma unit, more frequently due to drowsiness and dyspnea. Invasive procedures, probably unnecessary, were identified in 21.5% (37/172 patients), orotracheal intubation and central venous catheter for inotropic were the most frequent. The average stay in emergency department was eight days, with 32% of oncological deaths and 24% of non-oncological deaths in emergency department (p = 0.43). Conclusions: 10% of patients admitted to the emergency department of a tertiary hospital have chronic terminal disease, with a greater frequency of non-oncology, probably performing unnecessary procedures in one fifth of these.